MENINGKATKAN KEAKTIFAN BELAJAR SISWA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN LKPD - Mubarokah, Siti; Sulistyoningsih, Dwi; Roni, Aden (Litbang PWM Jawa Tengah, 2024)
This research is classroom action research (PTK). The aim of this research is to increase student activity by using a problem based learning model assisted by LKPD. The subjects in this research were all class VII students of SMP IT Hidayatul Mubtadiin Kebonagung. This research was carried out with indicators of positive activity and negative activity. The minimum work indicator for positive activities is 75% while the minimum work indicator is 15%. In cycle 1, the percentage of positive activity was 70% and negative activity was 20%. Because the minimum work indicators were not met, cycle 2 was carried out which resulted in a positive activity percentage of 80% and negative activity of 13%. These results show that the percentage obtained meets the criteria for research success, so it can be concluded that the application of the problem based learning model assisted by LKPD can increase student learning activity.